2013
DOI: 10.1088/0029-5515/53/12/123018
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of localized fast-ion heat loads in test blanket module simulation experiments on DIII-D

Abstract: Infrared imaging of hot spots induced by localized magnetic perturbations using the test blanket module (TBM) mock-up on DIII-D is in good agreement with beam-ion loss simulations. The hot spots were seen on the carbon protective tiles surrounding the TBM as they reached temperatures over 1000• C. The localization of the hot spots on the protective tiles is in fair agreement with fast-ion loss simulations using a range of codes: ASCOT, SPIRAL and OFMCs while the codes predicted peak heat loads that are within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Thus, it has been shown that the results of BBNBI+ASCOT coincide with those of NUBEAM for axisymmetric plasmas for both JET and AUG. Together with earlier 3D studies [6,7] these results further validate using BBNBI+ASCOT also for studying phenomena that require particle following in a truly three-dimensional geometry.…”
Section: Summary and Future Worksupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, it has been shown that the results of BBNBI+ASCOT coincide with those of NUBEAM for axisymmetric plasmas for both JET and AUG. Together with earlier 3D studies [6,7] these results further validate using BBNBI+ASCOT also for studying phenomena that require particle following in a truly three-dimensional geometry.…”
Section: Summary and Future Worksupporting
confidence: 72%
“…The particle following Monte Carlo code ASCOT [1,2,3] has been used to simulate NBI in several fusion devices including ITER [3], ASDEX Upgrade (AUG) [4], Joint European Torus (JET) [5,6], DIII-D [7], and TEXTOR [8]. Until recently, however, the initial test particle ensemble for ASCOT had to be obtained from an external code, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated [8] outward deflection of the vacuum magnetic field lines near the TBM is ≲2 mm, a value that is an order of magnitude smaller than the gap between the last-closed flux surface and the vessel wall. Localized heating is caused primarily by orbital deflections across field lines, not free-streaming along deflected field lines [6].…”
Section: Apparatusmentioning
confidence: 99%
“…During beam injection, localized heating on the graphite tiles that surround the TBM port is observed [5]. Initially, it was unclear whether this additional heating is caused by beam-ion impact or by increased heat flux from the bulk plasma but, in a follow-up experiment [6], 2 MW of beam power was replaced by 3.3 MW of electron cyclotron heating power in plasmas with the same plasma shape. Localized heating was only observed during neutral beam injection, definitively establishing that beam-ion losses are responsible.…”
Section: Introductionmentioning
confidence: 99%
“…Since lack of axisymmetry is directly translated into reduced confinement, alarm was sounded on possible wall damage due to localized losses of energetic alphas and/or NBI ions near the TBMs. This led to not only significant simulation efforts, but even experimental studies where the effect similar to that due to TBMs was produced by introducing mock-up coils behind the first wall tiles in the DIII-D tokamak (Kramer et al 2013).…”
Section: Tbm-mockup Experiments At Diii-dmentioning
confidence: 99%